2018
DOI: 10.1016/j.annemergmed.2017.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the Canadian CT Head Rule and Its Association With Use of Computed Tomography Among Patients With Head Injury

Abstract: Study objective Approximately 1 in 3 computed tomography (CT) scans performed for head injury may be avoidable. We evaluate the association of implementation of the Canadian CT Head Rule on head CT imaging in community emergency departments (EDs). Methods We conducted an interrupted time-series analysis of encounters from January 2014 to December 2015 in 13 Southern California EDs. Adult health plan members with a trauma diagnosis and Glasgow Coma Scale score at ED triage were included. A multicomponent inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 25 publications
2
49
1
1
Order By: Relevance
“…Traditional implementation strategies such as CDS can address clinical factors such as a lack of awareness of the evidence [ 37 ]. However, these strategies have had limited success for this decision, likely due to nonclinical factors such as patients’ concerns with their condition and care [ 12 - 15 ]. Findings of this study suggest that patients can be educated and engaged in the ED setting in decisions about CT imaging for low-risk minor head injury using a health information technology interface that supports the clinician-patient relationship (rather than getting in its way) [ 17 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional implementation strategies such as CDS can address clinical factors such as a lack of awareness of the evidence [ 37 ]. However, these strategies have had limited success for this decision, likely due to nonclinical factors such as patients’ concerns with their condition and care [ 12 - 15 ]. Findings of this study suggest that patients can be educated and engaged in the ED setting in decisions about CT imaging for low-risk minor head injury using a health information technology interface that supports the clinician-patient relationship (rather than getting in its way) [ 17 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Implementing the CCHR with traditional computerized clinical decision support (CDS) has had a modest effect (5%-8%) on decreasing CT use in these patients [ 12 , 13 ]. Since one-third of CTs in minor head injury patients are potentially avoidable and traditional CDS has had limited effect on reducing these scans, it has been hypothesized that nonclinical factors (such as fear of litigation, physician personality, fear of missed diagnoses, financial incentives, paucity of information, and patient expectations) also contribute to CT overuse in these patients [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…A significant challenge we encountered during the testing and implementation phase was integrating the checklist into existing workflows, given the busy environment of the ED. Traditionally, the CCTHR has been employed at the point of CT scan order entry, which occurs after the provider–patient interaction has occurred and therefore after the clinician (MD, NP or PA) has already committed to ordering diagnostic imaging 13 16. We felt that providing reminders and cues earlier in the care process would have a bigger impact on nudging clinician behaviour since it would allow them to incorporate the CCTHR as part of their assessment and engage patients in the process before committing to ordering a CT scan.…”
Section: Strategymentioning
confidence: 99%
“…The CCTHR is a widely accepted and well-validated clinical decision rule used for ED patients with minor head injuries. Several studies have shown the rule performs better than other clinical decision rules and is highly sensitive at detecting clinically significant head injuries 4 6 13–15. However, the effect of the CCTHR on reducing CT scan utilisation has yielded mixed results, with some studies showing decreased CT use with the CCTHR, while others showing increased use of CT scans post-implementation 6 16…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation